Optimization of the Fuse Protection System of The BT Electrical Distribution Network in Likasi in Order to Reduce Electric Arcs And Expenses (International Journal of Scientific Research and Management (IJSRM), 2025)
The study on the optimization of the fuse protection system of the BT electrical distribution network in Likasi has identified the main causes of the recurring electric arcs and the high expenses related to this system. The failures of the protection system are mainly due to a lack of coordination of the protections and a suboptimal selectivity of the installed fuses. This results in frequent power outages and significant maintenance costs for the network operator. To address this situation, technical and organizational solutions have been proposed. These include strengthening the coordination of the protections, optimizing the selectivity of the fuses and improving the preventive maintenance of the network. These improvements should significantly reduce the failures of the protection system, thus benefiting consumers in terms of the reliability of the electricity supply, and the operator in terms of controlling operating costs. Beyond these immediate solutions, the optimization of the fuse protection system is part of a continuous improvement perspective, particularly with the emergence of smart monitoring and control technologies. The progressive integration of more efficient protection devices, such as fast-acting fuses or electronic circuit breakers, will also help reduce the risks of electric arcs and optimize network maintenance. In the longer term, this optimization approach will have to adapt to the challenges of the local energy transition. In addition, an innovative solution was considered as part of this study: the recycling of zinc envelopes from used batteries for the manufacture of replacement fuses. This approach would not only reduce electric arcs, but also significantly reduce the costs associated with the purchase of new fuses. The dimensioning of these zinc fuses, based on the characteristics of the battery envelopes, would be an interesting avenue to explore to further optimize the protection system of the BT network in Likasi.